Lipodystrophy syndrome in HIV/aids patients (Revista Venezolana de Salud Pública, 2018)
To determine lipodystrophy syndrome (LDS) in HIV/AIDS patients attended in consultation the SIDA/ITS in the University Hospital “Dr. Miguel Oraá”, Guanare, Venezuela. A descriptive, ambipesctive study was conducted in a group of HVI/AIDS patients who received a combined anti-retroviral therapy. The information was collected from the clinical history and interviewing the patients. Eighty (80) patients were assessed; the mean age was 36.6 ± 12.0 years. The length of time using the combined anti-retroviral therapy varied (from less than 3 years to 15 years).
Keywords: lipodystrophy syndrome; HIV/AIDS; Combined Antiretroviral Therapy